A Study on the Issues of Power Quality in Power Systems - KBVSR Subrahmanyam, Dr.; Vedik, Bashetty.; Praveen Kumar, M.; Dhanraj, K. (International Journal of Engineering and Technology, 2018)
This paper shows a study on power quality problems related with the combination of sustainable power source frameworks into lattice and it exhibits how power electronic gadgets and Flexible AC Transmission Systems have an influence to alleviate the power quality problems. Photo Voltaic (PV) and Wind vitality frameworks joining issues and related power quality problems are discussed. Arrangement of different Power Quality Issues used by different scientists has been done and put for reference. Use of different systems as connected to relieve the various Power Quality problems is likewise displayed for thought. The vital point of this paper is to explore the most generally perceived power quality problems, the effect of the music on the power quality, the methods for assessing the measure of consonant reshaping appear in a power framework which prompt confine the reason for the issue lastly gadget an answer for a good power quality.Â Â